LST1 expression correlates with immune infiltration and predicts poor prognosis in acute myeloid leukemia - Haitao Xu; Dangui Chen; Jia Lu; Lihong Wang; Fei Chen; Long Zhong (Discover Oncology)
Abstract Clinical management of acute myeloid leukemia (AML) poses significant challenges due to its poor prognosis and heterogeneous nature. Discovering new biomarkers is crucial for improving risk assessment and customizing treatment approaches. While leukocyte-specific transcript 1 (LST1) is implicated in inflammation and immune regulation, its function in AML remains ambiguous. In this investigation, we conduct a comprehensive investigation into LST1 expression profiles, clinical implications, functional pathways, and immune interactions in AML, leveraging multi-omics data and experimental validations. Our examination shows increased levels of LST1 expression in AML when compared to regular hematopoietic tissues, a discovery validated by RT-qPCR and Western blot analyses in a separate group. Elevated LST1 levels correlate with distinct clinicopathological features, including increased white blood cell counts, non-M3 FAB subtype, and intermediate/poor cytogenetic risk. Importantly, heightened LST1 levels predict unfavorable overall survival outcomes across various subgroups, independently of age and cytogenetic risk. We develop an integrative nomogram incorporating LST1 expression, demonstrating robust prognostic efficacy for patient survival. Transcriptomic profiling identifies 275 differentially expressed genes between LST1-high and -low AML cases, enriched in cytokine signaling, immune modulation, cell adhesion, and oncogenic pathways. Furthermore, LST1 exhibits significant associations with the infiltration of diverse immune cell subsets within the AML microenvironment, particularly myeloid cells and regulatory T cells (Tregs). In conclusion, our study establishes LST1 as a novel prognostic indicator with immunological relevance in AML, emphasizing its potential therapeutic implications. Further mechanistic elucidation of LST1 in AML pathogenesis is crucial for its clinical translation.